Evaluation of two biosorbents in the removal of metal ions in aqueous using a pilot scale fixed-bed system - Oliveira, André G. (2021)
: The aim of the present work was to investigate the adsorption of toxic metal ions copper, nickel and zinc from aqueous solutions using low cost natural biomass (sugar cane bagasse and green coconut fiber) in pilot scale fixed-bed system. The Hydraulic retention time (HRT) was 229 minutes and the lowest adsorbent usage rate (AUR) found was 0.10 g.L-1 for copper using green coconut fibers. The highest values of adsorption capacities founded were 1.417 and 2.772 mg.g-1 of Cu(II) ions for sugarcane bagasse and green coconut fibers, respectively. The results showed that both sugarcane bagasse and green coconut fiber presented potential in the removal of metal ions copper, nickel and zinc ions from aqueous solution and the possible use in wastewater treatment station.